Synthesis of (−)-julocrotine and a diversity oriented Ugi-approach to analogues and probes - Ricardo A. W. Neves Filho (Beilstein Journal of Organic Chemistry, 2011)
An improved total synthesis of (−)-julocrotine in three steps from Cbz-glutamine, in 51% overall yield, is presented. To demonstrate the potential of the heterocyclic moiety for diversity oriented synthesis, a series of (−)-julocrotine analogues was synthesized by employing the heterocyclic precursor as an amino input in Ugi four-component reactions (Ugi-4CR) .